Septic patients in the intensive care unit present different nasal microbiotas. (26th February 2019) - Tan, Xi-lan; Liu, Hai-yue; Long, Jun; Jiang, Zhaofang; Luo, Yuemei; Zhao, Xin; Cai, Shumin; Zhong, Xiaozhu; Cen, Zhongran; Su, Jin; Zhou, Hongwei
Aim: The primary objective of this study was to evaluate correlations among mortality, intensive care unit (ICU) length of stay and airway microbiotas in septic patients.Materials & methods: A deep-sequencing analysis of the 16S rRNA gene V4 region was performed.Results: The nasal microbiota in septic patients was dominated by three nasal bacterial types ( Corynebacterium, Staphylococcus and Acinetobacter ). The Acinetobacter type was associated with the lowest diversity and longest length of stay (median: 9 days), and the Corynebacterium type was associated with the shortest length of stay. We found that the Acinetobacter type in the >9-day group was associated with the highest mortality (33%).Conclusion: Septic patients have three nasal microbiota types, and the nasal microbiota is related to the length of stay and mortality.